The Sponsor Effect - Hewlett, Sylvia (Ascent Audio, 2020)
Many people know the benefit of finding a sponsor-someone who goes beyond traditional mentorship to partner with a junior-level employee to help build their skills, advocate for them when opportunities arise, and open doors. But few realize that being a sponsor is just as important to career growth as finding one. According to new research from economist and thought leader Sylvia Ann Hewlett, senior executives who sponsor rising talent are 53 percent more likely to be promoted than those who don't. Similarly, middle-level managers who have proteges are 167 percent more likely to be given stretch assignments. Well-chosen proteges contribute stellar performance, steadfast loyalty, and capabilities that you, the sponsor, may lack, thus increasing how fast and how far you can go. But how do you find standout proteges, let alone develop them so that they're able to come through for you and your organization? This book has the answers you need. Combining powerful new data and rich examples drawn from in-depth interviews with leaders from companies such as Unilever, Aetna, Blizzard Entertainment, and EY, The Sponsor Effect provides a seven-step playbook for how you can become a successful sponsor.
Online resource; Title from title page (viewed October 20, 2020)
Keywords: Mentoring in business; Business; Leadership; Mentorat dans les affaires; Affaires; businesses (business enterprises); Audiobooks